Time in groups - Blount, Sally (Research on managing groups and teams ;, 2004)
Human experience can only be understood across the landscape of time. Yet organizational and groups research has traditionally paid little attention to time as a construct. Over the last 15 years, several authors have begun to study different aspects of group temporality, but these contributions have been published in disparate books and journals. As a result, no integrated set of readings or unified perspectives has emerged, and little research impact has been realized. The goal of this volume is to consolidate, integrate, and build upon existing research to create a framework for studying group temporality. The book approaches group temporality through four lenses: 1. The study of how group processes, such as relationship and trust building, information exchange, consensus building and performance, evolve over time 2.The study of how group members internally synchronize their activities over time and align them to meet the temporal demands of a group's constituents 3. The study of how time pressure affects members' cognitive functioning, interactions, and task performance 4. The study of how organizational context directs the nature of group temporality - both enhancing and impeding group flow. Together, the twelve chapters, authored by 27 leading groups scholars, lead the way in solidifying current understanding and highlighting critical new research directions.